Comparative evaluation of natural antioxidants spirulina and aloe vera for the treatment of oral submucous fibrosis - Santosh Patil; Bader Kureyem Al-Zarea; Sneha Maheshwari; Rohit Sahu (Elsevier, 2015)
Aim: Oral submucous fibrosis (OSMF) is a high risk premalignant condition predominantly seen in the Indian subcontinent. The aim of the present study was to compare the efficacy of spirulina and aloe vera in the management of OSMF. Material and methods: 42 subjects with clinico-pathologically diagnosed OSMF were included in the study and divided equally in 2 groups, Group A (spirulina group) and Group B (aloe vera group). Group A was administered 500 mg spirulina in 2 divided doses for 3 months and Group B was given 5 mg aloe vera gel to be applied topically thrice daily for 3 months. Evaluation for different clinical parameters was done at regular intervals and data was analyzed using the Chi-square test. P-value <0.05 was considered to be statistically significant. Results: The patients in Group A showed significant clinical improvement in mouth opening and ulcers/erosions/vesicles (p < 0.05). However, there was no significant improvement in burning sensation (p = 0.06) and pain associated with the lesion (p = 0.04) among the 2 groups. Conclusion: Both the drugs showed improvement in the condition; however spirulina can bring about significant clinical improvements in the symptoms like mouth opening and ulcers/erosion/vesicles. Thus, spirulina appears to be more promising when compared to aloe vera for the treatment of OSMF.